African exceptions: democratic development in small island states - Sanches, E.; Cheeseman, N.; Veenendaal, W.; Corbett, J. (Journal of International Relations and Development, 2022)
Small island states are much more likely to have democratic regimes than large continental states. This trend also holds across Africa, where the five island states with populations of 1.5 million or less are all rated at least ‘partly free’ by Freedom House. In this article we explore what it is about being a small island state that might explain this trend. Building on studies from other small island states, we find that the interaction between the two contextual factors is key to explaining their diversion from mainland trends in the African context. Specifically, ‘smallness’ leads to closer links between citizens and politicians in addition to more effective service delivery, while ‘islandness’ promotes community cohesion and provides a buffer against instability and conflict in neighbouring states. This results in a positive feedback loop that guards against authoritarian excess. Our focus on population size and geography thus adds to the existing studies of the contextual drivers of African democratisation.